Analisis Tren Harga Aluminium, Tembaga, dan Nikel 2015–2025 serta Implikasinya terhadap Biaya Material Manufaktur - Ramadhan, Gilang; Riawan, Ibnu Azmi; Naim, Raihan Deprija (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This research analyzes the price trends of aluminum, copper, and nickel during the period 2015–2025 and their implications for the cost of manufacturing materials in Indonesia. This study examines the increasing volatility of global metal prices, which directly impacts the cost structure of the manufacturing industry. The research aims to identify price change patterns for the three metals and examine their impact on manufacturing material costs. This research uses a quantitative approach with secondary data consisting of metal prices from the London Metal Exchange and Kitco Metals, as well as sales and material cost data from national metal distribution company reports. The analysis was conducted using descriptive analysis and multiple linear regression. The research findings indicate that the increase in metal prices, particularly after 2020, has a significant impact on the rise in manufacturing material costs, with nickel exerting the greatest cost pressure. This research recommends strengthening the downstream metal industry to reduce dependence on global price fluctuations.